Review paperGenetic factors in aetiopathogenesis of acne vulgaris - Sobjanek, Michał; Zabłotna, Monika; Sokołowska-Wojdyło, Małgorzata; Nedoszytko, Bogusław; Michajłowski, Igor (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2007)
Acne vulgaris is one of the most common skin disorders. Prevalence is reported at between 35% and 90% in adolescents. The pathogenesis of acne is complex, multifactorial and still unclear. The genetic influence on pathogenesis of acne is well documented in the case of twins and in genealogic studies. There are only a few reports concentrating on the association between acne and genes. The relationship of acne and HLA, CYP1A1, CYP17, CYP21, MUC1, AR and MC5-R genes was investigated. We present a review of the role of genetic factors in the aetiopathogenesis of acne. Key words: acne vulgaris, genetic factors.